Embracing electronic learning in medical education during COVID-19 pandemic - Bista, Soni; Basnyat, Rupesh Shingh; Ranjit, Rebicca; Subedi, Nuwadatta (Journal of Gandaki Medical College-Nepal, 2021)
Medical education is considered as a very significant strategy ensuring good quality in academics and health care. Currently, medical education across the world has been experiencing a major obstruction as a consequence of the novel coronavirus disease pandemic. At the same time, the rapid use of emergent technologies to maintain effective teaching and learning has become an essential component for transformative changes and the future of medical education. In this paper, we discuss the role of e-learning in medical education by outlining its components, effectiveness, barriers, all the pros and cons and future of implementation of such technology. The intention of this article is to inform all medical educators and students across the world on how the technological changes even after the pandemic can have a positive impact on medical education.